An algorithm for the number of path homomorphisms - Srichan Arworn (2018)
A homomorphism of a graph G1= (V1, E1) to a graph G2= (V2, E2) is a mapping from the vertex set V1of G1to the vertex set V2of G2which preserves edges. In this paper we provide an algorithm to determine the number of homomorphisms from an arbitrary finite undirected path to another arbitrary finite undirected path. © 2008 Elsevier B.V. All rights reserved.